Organic Production of Tuberous Vegetables: Agronomic, Nutritional and Economic Benefits - Suja, G.; Sreekumar, J; John, K Susan; Sundaresan, S (JOURNAL OF ROOT CROPS, 2013)
Global awareness of health and environmental issues has stimulated interest in alternative agricultural systems like organic farming. Elephant foot yam (Amorphophallus paeoniifolius) and yams (Dioscorea spp.) are ethnic starchy vegetables with high energy, nutritive and medicinal values. Field experiments were conducted at the Central Tuber Crops Research Institute, Thiruvananthapuram, India, during 2004-2011 to assess the agronomic, nutritional and economic advantages of organic farming over conventional system in these crops. Organic farming resulted in 10-20% higher yield over conventional practice in these crops. A net profit of Rs 2,15,776 ha-1, which was 28% higher over chemical based farming was obtained under organic management in elephant foot yam. Elite and local varieties responded equally well to organic and conventional farming in elephant foot yam. White yam, greater yam and lesser yam responded similarly to both the systems, with slightly higher yield under organic practice. Soil physico-chemical properties and microbial count were also improved under organic management. Organic farming scored significantly higher soil quality index (1.93) than conventional practice (1.46). The soil quality index was driven by water holding capacity, pH and available Zn followed by soil organic matter. Tuber quality was improved with higher dry matter, starch, crude protein and lower oxalate contents. Cost effective technologies were field validated.